Stroke subtype-dependent synapse elimination by reactive gliosis in mice - Xiaojing Shi (Nature Portfolio, 2021)
Microglia and astrocytes clear neuronal debris after stroke, whether glia remain phagocytic and cause synapse loss at the subacute stage remains unknown. Here, the authors show in a murine model of ischemic stroke that inhibition of phagocytosis by MEGF10 and MERTK deletion in microglia and astrocytes attenuated damage and improved neurological outcomes by preventing synapse loss.